Cognitive Destination Image and Tourist Satisfaction: The Case of the Fruit Festival in Thailand - Mustafa Daskin; Kübra Aşan (Journal of Tourism, Sustainability and Well-being, 2022)
This research study aims to examine the association between cognitive destination image (CDI) attributes and tourist satisfaction. Data for the present research work was attained from a sample of tourists at Sisaket Fruit Festival/Thailand. Participants self-managed the questionnaires. A total number of 110 usable questionnaires were collected in the survey context. Bootstrapping technique by Partial Least Square-PLS in conjunction with SPSS 23 was used to analyze the data. The path analyses show that the CDI attributes were found positively related to tourist satisfaction at different levels. Additionally, based on the analyses of demographic comparisons, foreign tourists were found to be more satisfied with the festival through their participation in the study was much less than the Thai tourists. Public jobholders were more satisfied compared to the private jobholders and the student participants. This study contributes to tourism literature and has helpful implications for the industry in terms of developing fruit festivals and fairs.